Aplikasi Bakteri Asam Laktat dari Inasua sebagai Biopreservatif Ikan Patin (Pangasius sp.) : Lactic Acid Bacteria Aplication from Inasua As Biopreservative for Catfish (Pangasius sp.) - Meilany Ariati Dewi; Nisa Rachmania Mubarik; Desniar Desniar; Sri Budiarti (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Lactic Acid Bacteria or LAB are bacteria that are categorized as generally recognized as safe (GRAS) because they are safe for human health and are non-pathogenic, so they have the potential to be biopreservative. Several metabolic products produced by LAB have antibacterial properties, including bacteriocin, diacetyl, hydrogen peroxide and organic acids. Isolates of L. plantarum IN05 and L. rhamnosus IN13 isolated from fermented inasua food were studied for their potential as biopreservatives because of their antibacterial properties. The content of animal protein in fish is in great demand by the public, one of which is catfish which is in great demand by the public, but catfish is easy to damage and decrease in quality. This is due to the presence of the pathogenic bacterium Listeria monocytogenes which has the ability to grow at cold storage temperatures (refrigeration) to freezing. This study aimed to apply a neutral cell-free supernatant, cell-free supernatant, and bacterial cell biomass from L. rhamnosus IN13 and L. plantarum IN05 isolates and formalin in storage of catfish fillets contaminated with Listeria monocytogenes bacteria. The methods used include the production of antibacterial compounds, determination of the sensitivity of antibacterial compounds to test bacteria, confirmation test of antibacterial compounds with the addition of proteinase K, application of antibacterial compounds to catfish fillets, calculation of total bacterial colonies, bacterial colonies of L. monocytogenes, and lactic acid bacteria, as well as measurement of the pH value of catfish fillet. The SBSN antibacterial compound from L. rhamnosus IN13 has the ability to maintain catfish fillets for up to 14 days of storage in accordance with the requirements for fresh fish that are suitable for consumption according to the 2017 SNI standard on general requirements and guidelines for microbiological testing. The total microbial value was 5.65 log CFU/g, the pH value of catfish fillet meat was 6.37, and the total value of L. monocytogenes bacteria decreased during storage time.